Biological and synthetic surfactant exposure increases antimicrobial gene occurrence in a freshwater mixed microbial biofilm environment. Issue 2 (17th March 2023) - Gill, Stephanie P.; Snelling, William J.; Dooley, James S. G.; Ternan, Nigel G.; Banat, Ibrahim M.; Arnscheidt, Joerg; Hunter, William R.
Abstract: Aquatic habitats are particularly susceptible to chemical pollution, such as antimicrobials, from domestic, agricultural, and industrial sources. This has led to the rapid increase of antimicrobial resistance (AMR) gene prevalence. Alternate approaches to counteract pathogenic bacteria are in development including synthetic and biological surfactants such as sodium dodecyl sulfate (SDS) and rhamnolipids. In the aquatic environment, these surfactants may be present as pollutants with the potential to affect biofilm formation and AMR gene occurrence. We tested the effects of rhamnolipid and SDS on aquatic biofilms in a freshwater stream in Northern Ireland. We grew biofilms on contaminant exposure substrates deployed within the stream over 4 weeks. We then extracted DNA and carried out shotgun sequencing using a MinION portable sequencer to determine microbial community composition, with 16S rRNA analyses (64, 678 classifiable reads identified), and AMR gene occurrence (81 instances of AMR genes over 9 AMR gene classes) through a metagenomic analysis. There were no significant changes in community composition within all systems; however, biofilm exposed to rhamnolipid had a greater number of unique taxa as compared to SDS treatments and controls. AMR gene prevalence was higher in surfactant‐treated biofilms, although not significant, with biofilm exposed to rhamnolipids having the highest presence of AMR genes and classes compared to the control or SDS treatments. Our results suggest that the presence of rhamnolipid encourages an increase in the prevalence of AMR genes in biofilms produced in mixed‐use water bodies. Abstract : Biofilms exposed to biological and synthetic surfactants may experience an increased prevalence of antimicrobial resistance genes. Of the nine total classes tested, eight were present in biofilm exposed to a biological surfactant, five were present after exposure to a synthetic surfactant, and four were present in our control.